REGIONAL STATISTICAL GROUPING OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (Marketing Journal, 2025)
The main indicators of the innovative activity of small business and private entrepreneurship, the territorial structure of innovative goods, works, and services produced by enterprises in this area, and the dynamics of labor productivity are described.
Keywords: labor productivity; small business; private entrepreneurship; innovative activity